An In-school-based program of combined fine motor exercise and educational activities for children with neurodevelopmental disorders - Szturm, T; Polyzoi, E; Marotta, J; Srikesavan, C (Mary Ann Liebert, 2014)
This article introduces a game-based rehabilitation platform designed to integrate training of fine motor skills and cognitive functions. A novel computer interface device was developed that can effectively replace a standard computer mouse when doing exercises to rehabilitate hand function. This smart device converts signals from miniature motion sensors to signals equivalent to that of a computer mouse. In this way, nearly any object or utensil can be changed to function exactly as a computer mouse, simply by attaching the motion sensor. Multiple objects with varied sizes, shapes, weights, and functional demands for precision can be used for exercise and to practice a variety of gross or fine motor skills, and, importantly, while playing fun computer games. The platform was designed to work with modern and common computer games, which have a broad range of movement speeds and accuracy levels, cognitive activities (puzzles, choices, distractors), and educational content. The platform includes a designed assessment game with advanced data logging for electronic monitoring. Data analysis methods have been developed to quantify performance metrics that provide insights into the quality, efficiency, and skill of a child and thus mean to conduct trend analyses that indicate how the child is performing over time.